Dampak Tax Amnesty, Kesadaran Wajib Pajak, Pertumbuhan Ekonomi Dan Sosialisasi Perpajakan Terhadap Kedisiplinan Wajib Pajak Orang Pribadi Di Wilayah Kota Serang - Raden Irna Afriani; Aris Trismayadi Nurizki; Firdha Destiani (Universitas Sultan Ageng Tirtayasa, 2025)
Serang City still faces challenges in the tax sector. To improve tax revenue and taxpayer discipline, this study analyzes the impact of the tax amnesty program, taxpayer awareness, economic growth, and tax socialization on individual taxpayer discipline. Using a quantitative method with multiple linear regression, data were collected through questionnaires distributed to registered individual taxpayers in Serang City and processed using SPSS version 27. The results show that tax amnesty (X1), taxpayer awareness (X2), and tax socialization (X4) significantly affect taxpayer discipline, with t-values of 2.556, 2.135, and 2.102 (all > 1.983). However, economic growth (X3) has no significant effect (t = 0.019 < 1.983). Simultaneously, all variables significantly influence taxpayer discipline (F = 13.068 > 2.69). Therefore, tax amnesty, taxpayer awareness, and tax socialization are key factors affecting taxpayer discipline in Serang City.